Paternal Incarceration, Family Relationships, and Adolescents’ Internalizing and Externalizing Problem Behaviors - Venema, Simon D. (Journal of developmental and life-course criminology, 2024)
Little is known about the conditions under which paternal incarceration is harmful to children and the mechanisms that explain this. This study addressed the family relationship context in the associations between paternal incarceration and adolescents’ internalizing and externalizing problem behaviors. Using data from the Future of Families and Child Wellbeing Study, a moderated mediation model was specified where paternal incarceration predicted adolescents’ internalizing and externalizing problem behaviors through family relationship quality, and where the mediating role of family relationship quality was moderated by pre-incarceration family relationship characteristics. Using latent profile analyses, three pre-incarceration family clusters were identified (“Cohesive”; “Fragmented”; “Disharmonious”). Analyses indicated that the association between paternal incarceration and family relationship quality differed across pre-incarceration family clusters and that decreased father-mother relationship quality mediated the negative association between paternal incarceration and adolescents’ internalizing and externalizing problem behaviors among “Cohesive” and “Fragmented”, but not among “Disharmonious” family clusters. The findings suggest that adolescents with more harmonious pre-incarceration family relationships are most vulnerable to the negative consequences of paternal incarceration. The study demonstrates the need to consider the family relationship context to understand the intergenerational consequences of incarceration.